Global spread of drug-resistant Acinetobacter baumannii: molecular epidemiology and management of antimicrobial resistance. (April 2011) - Durante-Mangoni, Emanuele; Zarrilli, Raffaele
Acinetobacter baumannii is an opportunistic Gram-negative pathogen with increasing relevance in a variety of hospital-acquired infections especially among intensive care unit patients. Resistance to antimicrobial agents is the main reason for A. baumannii spread. A. baumannii outbreaks described worldwide are caused by a limited number of genotypic clusters of multidrug-resistant strains that successfully spread among hospitals of different cities and countries. In this article, we will focus on the mechanisms responsible for resistance to antimicrobials and disinfectants in A. baumannii and the epidemiology of drug-resistant A. baumannii in healthcare facilities. We will also discuss the therapeutic and infection control strategies for management of drug-resistant A. baumannii epidemics.